Developing Social Partnership In Community Working With Children At Risk - Stuopyte, Edita (European Scientific Journal, ESJ, 2016)
When rendering social educational assistance in community (on selfgovernment level), coordination of activities of different institutions working with risk group children is important: in order to attain this goal development of social partnership is one of the ways. The aim of the article is disclose development of social partnership when working with children at risk in community. In order to attain this aim three objectives were formulated. While implementing the first objective, the conception of risk group children, factors of emergence of this socially vulnerable group are discussed; the second – theoretical assumptions for social partnership in community while working with children at risk are disclosed and the third – the viewpoint of the specialists (social pedagogues and social workers), who work with children at risk in community, to development of social partnership is identified. Research methods: analysis of scientific literature, semi-structured interview. Twelve specialists (social pedagogues and social workers), who work with risk group children in community, were interviewed by the qualitative method (semi-structured interview).